Immediate effects of diode laser (970±15 nm) on microbial load in patients with chronic periodontitis: A split-mouth study - Kavita Chandrasekaran; Sunil Kumar D Chavan; Krishna Kripal; P Anuroopa (Wolters Kluwer Medknow Publications, 2021)
Background: Periodontitis is a multifactorial disease, and the causative periodontal pathogens have been detected in patient samples like plaque, gingival crevicular fluid (GCF), saliva, crevicular blood, gingival tissues, etc. Laser disinfection is an advanced treatment that has been shown to alter the bacterial flora and have greater efficacy in reducing the progression of the disease. Aim: This study is aimed to evaluate the immediate effects of a diode laser (970 ± 15 nm) on the microbial load in GCF, crevicular blood, and saliva samples of patients suffering from chronic periodontitis. Materials and Methods: A total of 45 subjects were recruited for the study. Each patient's mouth was divided equally into two halves, which were allotted randomly into two groups. In group I (test group), diode laser disinfection was performed, and in group II (control group), saline irrigation was performed. The GCF, saliva, and crevicular blood samples were collected before and immediately after disinfection for microbial analysis. Results: Clinical observations showed a reduction in microbial load in both groups, which were statistically significant in the test group. GCF and saliva samples showed greater reduction when compared with crevicular blood samples in both groups. Conclusion: This study concludes that the application of diode laser (970 ± 15 nm) has immediate reducing effects on the microbial load in GCF, crevicular blood, and saliva samples in patients with chronic periodontitis.